Exploring Factors Influencing Work Productivity: A Qualitative Case Study of Employee Motivation and Leadership Practices - Sarwar Khawaja; Hengameh Karimi (Business, Management and Economics: Research Progress Vol. 4, 2024)
Work productivity is essential for organisational success, yet the reasons for varying levels of productivity among individuals are still not fully understood. This qualitative case study explores the elements that impact employee productivity and leadership practices through an examination of a private Business College’s Headquarter office in England. The study investigates motivational factors and engagement techniques used in this office through interviews with personnel and management. By studying real-world examples like this private business college, this research develops our understanding of productivity and leadership in contemporary business environments. The research aims to investigate the complex factors influencing employee productivity by drawing on motivational theories such as Self-determination Theory and Expectancy Theory, as well as insights from leadership literature on transformational leadership and employee engagement. Early findings indicate that internal motivators, such as autonomy, competency, and purpose, are crucial in enhancing employee productivity. Leadership styles that exhibit empathy, honesty, and a shared vision promote trust and cooperation, leading to increased employee engagement and performance. This research intends to provide important insights into employee productivity and leadership practices in the Headquarter office of a private business college setting by using a qualitative case study technique.